Perkembangan Bisnis e-Commerce dan Sistem Informasi Berbasis Teknologi: Implikasinya terhadap Kebutuhan Jasa Audit E-Commerce - Ni Kadek Devi Dwinasari; Ni Luh Putu Tariningsih; Ni Putu Eka Widyantari; Partiwi Dwi Astuti (Yayasan Literasi Ilmiah Indonesia, 2026)
Purpose: This study aims to examine the development of e-commerce businesses and technology-based accounting systems and their impact on the need for e-commerce audit services. Method: The population of this study comprises all auditors of public accounting firms in the Province of Bali, totaling 132 people, registered with the Indonesian Institute of Public Accountants in 2023. The sample for this study consisted of 56 people, selected using the purposive sampling technique. The data source used is primary data obtained from research respondents. The data collection technique used was a questionnaire. The data were analyzed using multiple linear regression techniques in SPSS 26. Finding: The results of the study show that the development of the e-commerce business has a positive, insignificant effect on the need for e-commerce audit services, and that technology-based accounting systems have a significant positive effect on the need for e-commerce audit services. Novelty: The study examines the relationship between the development of e-commerce businesses and technology-based accounting systems, and their implications for the need for e-commerce audit services, based on the technology acceptance model, which differs from previous studies that use the theory of planned behavior.